Komunikasi Informasi Edukasi Media Leaflet terhadap Pengetahuan dan Sikap Ibu Hamil Trimester I tentang Pemeriksaan Laboratorium - Yeti Ida Sumarni; Putri Azzahroh; Suprihatin Suprihatin (Universitas Baiturrahim, 2023)
The frequency coverage of ANC I in the first trimester, at least I time in thesecond trimester and at least II times in the third trimester is 70,4% and the coverage of KIE provision during the first trimester ANC is 81,6%. Early detection of pregnancy can be used as an effort to increase the knowledge and attitudes of pregnant women by providing early knowledge and attitudes of pregnant women by providing early knowledge about their pregnancy through leaflets. Objectives: to determine the effectiveness of educational information communication (KIE) leaflet media on the knowledge and attitudes of pregnant women about for first trimester laboratory examinations at PMB T, Bogor Regency in 2022.Methodology using a pre-experimental design with a one group pretest-posttest approach. The research sample was 30 pregnant women who visited PMB T in Bogor Regency in the period March to June 2022. The research instrument used leaflets, SAP, and questionnaires.Results are the effectiveness of IEC leaflet media on knowledge (p value = 0.001 0.05), and attitudes (p value = 0.001 0.05) pregnant women about the first trimester laboratory examination at PMB T,s Bogor Regency in 2022.Conclusion is the effectiveness of educational information communication (KIE) leaflet media on the knowledge and attitudes of pregnant women about screening first trimester laboratory examinations at PMB T, Bogor Regency in 2022. It is expected to further increase knowledge and skills about the initial of the first trimester laboratory examinations by attending counseling, health education or consultation with health workers, so that they can carry out initial of first trimester laboratory examinations independently and correctly to improve the health status of their babies and reduce mortality. mother and baby